Studi Eksperimental Pengaruh Penambahan Flywheel Pada Sistem Penggerak Mesin Las Gesek Rotari Terhadap Hasil Pengelasan Material Mild Steel Dengan Stainless Steel 201 - Devid Vio Sandri; Yohanes Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Friction welding including solid state welding type, Which the welding process is done in solid phase. Based on observation and research, The biggest cause of damage to the motor is overheating. To minimize overheating on the electric motor needs to be in added flywheel. The purpose of this research is to know the effect of adding flywheel to welding result and to know the optimal flywheel of three variations flywheel used with the diameter of 250 mm and thickness of 10 mm, 20 mm and 30 mm. Tests were performed on stainless steel type 201 material. To calculate ultimate tensile strength on the rotary swipe weld joint To calculate the ultimate tensile strength of the friction welding connection, a tensile test using Universal Testing Machine. Tests on welding specimens with three variations of flywheel obtained the highest average maximum tensile strength value using flywheel 3 with a value of 438.12 Mpa and the lowest average maximum tensile strength value was obtained on the welding specimens using flywheel 1 with a value of 418.12 Mpa. Flywheel 3 with a mass of 11.017 kg has better shock load holding capability than flywheel 1 with mass 3,8836 kg and flywheel 2 with mass of 7,4502 kg.Keywords : Friction Welding, Flywheel, Tensile Test.